Pembuatan kompos dari daun lamtoro dan serbuk kayu di Green House Universitas Sulawesi Barat sebagai media pembelajaran bagi mahasiswa - Maldrian, Maldrian; Munira, Munira; Mardini, Eki; Hasanah, Agna Khaeratul; Ferdi, Ferdi; Haidir, Haidir; Nurham, Nurham; Sinta, Sinta; Aulia, Husnul; Audy, Audy; Diat, Diat; Juliati, Juliati; Nurmasita, Nurmasita (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2025)
Using inorganic fertilizers can increase crop productivity, but excessive and continuous use can degrade soil and cause environmental pollution. To overcome this problem, compost from lamtoro (Leucaena leucocephala) leaves can be an environmentally friendly alternative solution. This activity aims to explain the process of making lamtoro leaf compost and its impact on soil fertility and plant growth. Through this activity, organic fertilizer has been produced in the form of compost from lamtoro leaves and wood dust, which is suitable for use as fertilizer. The manufacturing process includes collection, chopping, mixing with an organic activator, and fermentation until the compost is mature. From this activity, students can gain a direct understanding of compost production and the importance of using local organic materials for sustainable agriculture.